HEALTHCARE WASTE MANAGEMENT PRACTICES IN SELECTED HEALTHCARE FACILITIES: A QUANTITATIVE CROSS-SECTIONAL DESCRIPTIVE STUDY (Proceedings of the Global Public Health Conference, 2023)
The management of healthcare waste, known as Health Care Waste Management (HCWM), is an essential component of maintaining hygiene and proper upkeep within health facilities. This includes tasks such as the collection, transportation, treatment, and disposal of waste. Unfortunately, in developing countries like Nepal, poor HCWM practices pose a significant public health risk. Sadly, HCWM has not been prioritized, and has only received sporadic attention in recent years. In numerous instances, healthcare waste is disposed of through burning in metal drums or openly, leading to the release of toxic by-products into the environment. In Nepal, inadequate HCWM practices contribute to a range of health hazards, such as needle stick injuries (NSI) or other sharps injuries that can cause Hepatitis B, Hepatitis C, and HIV, as well as other health risks such as hemorrhagic fevers, skin infections, and gastroenteric infections. This study aimed to assess the practices of Health Care Waste Management (HCWM) in a specifically chosen health facility (HF) located in the Kailali district of Nepal. The research employed a descriptive cross-sectional study design and a quantitative method, in addition to a review and analysis of relevant literature and previous studies. The health facilities included in the study were both hospitals and health posts. The study employed an exploratory approach, and a purposive sampling method was used, where a total of 10 health facilities were visited; 5 government-run facilities and 5 private facilities. A semi-structured questionnaire was used to gather data, and responsible individuals from the institutions were interviewed regarding HCWM. On average, the ten health institutions (HI) generated 9 kg of waste per day. Out of the ten HIs, only five provided training in HCWM. Three HIs did not have guidelines for healthcare waste management and only four had waste management plans. Only one HI ensured that their waste handlers wore the necessary Personal Protective Equipment (PPE). Furthermore, nine out of the ten HIs did not have a monitoring system in place for HCWM. These findings highlight the need for mandatory training in HCWM for all responsible parties and the implementation of strict rules and regulations requiring the use of complete and necessary PPE by all responsible persons and waste handlers. Such measures would help prevent and protect against needle stick injuries and other diseases.
Keywords: Health Care Waste Management; Health Institution; Waste Handlers; Personal Protective Equipment